Effectivity Analysis of COVID-19 Vaccines Against Emerging Variants of SARS-CoV-2 - Saeed, Umar; Piracha, Zahra Zahid; Ashraf, Hafsa; Tasneem, Saba; Uppal, Sara Rizwan; Islam, Tabinda; Fatima, Maheen; Abid, Arooj; Uppal, Rehan; Uppal, Rizwan (Archives of Clinical and Biomedical Research, 2022)
SARS-CoV-2 is an mRNA virus that has plunged the whole world into serious trouble for the last two years. Due to continuous transmission, the virus mutates rapidly and new strains emerged which made vaccines less effective. The study aims to describe the impact of major vaccines on different variants of COVID-19. The successful launch of the COVID-19 vaccine raised hope for the extinction of pandemics and return to pre-quarantine life around the globe. Clinical trials revealed all major vaccines provide a short-term satisfactory level of protection against the disease but none of the vaccines is ensuring 100% safety against all variants. Efficacy drop of several vaccines has also been observed against the B.1.1.7, B.1.617, B.1.351 P.1 variants of concern. Phase 3 and phase 4 clinical trials need to be conducted on major vaccines. Chinese vaccines are expected to be most effective against the delta strain yet having no satisfactory results against SOIY.V2, B.1.1.7, and P.1 strains. While the western world has a hawk-eye on mRNA vaccines (BNT162b2 and mRNA-1273) having the highest efficacy rate (around 90-95%). Sputnik V vaccine is recently approved for use in more than 66 countries but its effectiveness against all variants of concern (VOC) is not guaranteed. The analysis revealed that overall vaccination is capable to provide 72% efficacy in terms of protection against deaths. None of the vaccines proved to be 100 % effective against all strains of COVID-19 but developed antibodies to fight better and increased chances of survival.